Simulation of stent retriever thrombectomy in acute ischemic stroke by finite element analysis. Issue 7 (19th May 2022) - Liu, Ronghui; Jin, Chang; Wang, Lizhen; Yang, Yisong; Fan, Yubo; Wang, Weidong
Abstract: Stent retriever thrombectomy has become an effective method for treating acute ischemic stroke. Successful recanalization cannot be achieved for all patients. The outcome of mechanical thrombectomy may be associated with some mechanical factors, requiring efficient tools that are able to assess the interaction between stent retrievers and clots. In this study, a simulation by finite element analysis was developed to evaluate the outcome of stent retriever thrombectomy for clots of different sizes and frictional properties. The deployment and retrieval of the stent retriever were conducted in a middle cerebral artery model. The recanalization, deformation of the clot and stent retriever and the stress induced in the clot were assessed. The results showed that higher friction could lead to failed recanalization and increased stress in the clot. The simulation method can be used to characterize the mechanical behaviour of stent retrievers and clots, offering a potential tool for the optimization of device design and the selection of surgical strategies.